Концепція змішаного навчання та комунікативний підхід: особливості імплементації у викладанні іноземної мови студентам нефілологічних спеціальностей у ЗВО - Малик Юліана; Malyk Yuliana; Никитенко Ольга; Nikytenko Olga; Ковальова Олена (Видавництво «Код», 2025)
Резюме. Сучасна позиція нашої держави викликає увагу до змішаного навчання у зв’язку з воєнною ситуацією. У дослідженні виокремлено основні форми викладу навчального матеріалу у навчальному середовищі для вивчення іноземної мови студентами нефілологічних спеціальностей у ЗВО. Засобами досягнення навчальних цілей за методикою змішаного навчання є два типи навчальних платформ, що описані у статті. В основі комунікативного підходу лежить мовленнєва компетенція як мета викладання мови і методи викладання іноземної мови студентам нефілологічних спеціальностей у ЗВО, як засіб досягнення даної мети.

Abstract. The current position of our state draws attention to blended learning in connection with the military situation, proves the significant expansion of international cooperation, the enrichment of international relations with countries of near and far abroad, the participation of Ukrainians in many international programs and projects, and the motivation of all countries of the world to support Ukraine’s peace initiatives. All this confirms the importance of a foreign language, causes an increase in interest in its study, notes the need to master foreign languages for the purpose of business communication, and also emphasizes the importance of mastering a foreign language at all levels, starting from secondary education institutions. The mechanism for implementing the concept of blended learning as a process involves the creation of a comfortable educational information environment, a communication system that presents all the necessary educational information. For use in a modern educational environment, three main components of the blended learning model have been identified: face-to-face learning; self-study learning; online collaborative learning. The means of achieving educational goals using the blended learning method are two types of educational platforms, which are described in the article. The main forms of presenting educational material in the educational environment for studying a foreign language by students of non-philological specialties in higher education institutions are identified. The communicative approach is based on speech competence as the goal of language teaching and methods of teaching a foreign language to students of non-philological specialties in higher education institutions as a means of achieving this goal. The principles on which the communicative approach is based are revealed. The main advantages of blended learning for students of non-philological specialties in higher education institutions are described.
The concept of blended learning and communicative approach: implementation features in teaching a foreign language to students of non-philology specialties in higher educational universities
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: змішане навчання; комунікативний підхід; викладання іноземної мови; студенти нефілологічних спеціальностей; ЗВО